Sinus Surgery : Endoscopic and Microscopic Approaches. - Levine, Howard L. (Thieme, 2011)
Taking a practical, ''in the trenches approach'' to diagnosing and treating nasal and sinus disorders, this book offers the expertise of world-renowned otolaryngologists-head and neck surgeons. From physiology and immunology of the sinuses to anatomic considerations and new radiologic techniques, the book covers all the topics the specialist must master in everyday practice. It includes more than 450 clear illustrations for easy visualization of complex sinus anatomy. In-depth discussions of minimally invasive, laser, stereotactic, and combined endoscopic and microscopic techniques make th.